Magnetic, morphological, optical, and EMI shielding assessment of Ti, Co, Mn, and Ni‑doped barium hexaferrite nanocomposites for X‑band applications - Katibi, Kamil Kayode; Azis, Rabaah Syahidah; Chen, Hongxu; Ibrahim, Garba Shitu; Ismail, Ismayadi; Muhammad, Farah Diana; Chan, Kar Tim; Mohamed Nafis, Nur Biha (Springer, 2025)
With the rapid growth of telecommunications, electromagnetic pollution and interference (EMI) have become critical challenges. This study developed barium hexaferrite-based nanocomposites doped with Ti, Co, Mn, and Ni to enhance EMI shielding capabilities. The nanocomposites (BaFe12O19 and the modified BaTiCoMn0.25Ni0.25Fe10O19) were synthesized using mechanical milling and thermal processing. Advanced analytical techniques such as x-ray diffraction, scanning and transmission electron microscopy, and vector network analysis confirmed the successful incorporation of dopants and revealed remarkable improvements. The BaTiCoMn0.25Ni0.25Fe10O19 variant exhibited enhanced magnetic properties with a coercivity of 308.9 Oe and magnetization of 65.9 emu/g, surpassing BaFe12O19. The optical band gap was increased to 2.3 eV, suitable for high-energy applications. The nanocomposite demonstrated superior EMI shielding, achieving a reflection loss of − 25.0 dB at 10.5 GHz and shielding effectiveness up to − 45.0 dB in the X-band (8.0–12.0 GHz), making it highly efficient for advanced EMI shielding in electronics and telecommunications.